WORKSHOP PENINGKATAN KOMPETENSI GURU MELALUI PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL BERBASIS GOOGLE SITES - Harmi Ibnu Dja'far; Maria Cleopatra; Dulhamin Arif; Bunga; Kurniasari Ambar; Minerva Anindyta; Nurzeini Herdiansyah (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2026)
Digital transformation in education requires teachers to master technological literacy and integrate digital learning media. This study aims to enhance the competencies of teachers at SMAN 2 Lembang through a workshop focused on developing Google Sites as a learning medium. The implementation methods included observation, focus group discussions, training, hands-on practice, mentoring, and data-driven evaluation. A total of 38 teachers participated in the activity, while implementation was evaluated through a questionnaire administered to 32 students. The results showed that 75% of teachers achieved a rating of good to very good in their use of Google Sites, as indicated by students’ scores falling within the high range. Teachers were able to produce digital works in the form of learning sites integrated with multimedia. Conducting the workshop online via Zoom enhanced learning flexibility and participant engagement. This activity made a significant contribution to improving teachers’ digital competencies and supported the implementation of hybrid learning as well as Open High School learning. The study concluded that the Google Sites workshop is effective as a strategy for strengthening teachers’ competencies and needs to be conducted continuously to ensure the sustainability of digital innovation in schools. Keywords: Teacher competencies, Google Sites, Digital learning, Workshop, Technological Transformation